A new approach to Legendre-truncated-exponential-based Sheffer sequences via Riordan arrays - Srivastava, H. M.; Riyasat, Mumtaz; Khan, Subuhi; Araci, Serkan; Acikgoz, Mehmet; Aracı, Serkan (Elsevier Inc., 2020)
The significance of multi-variable special polynomials has been identified both in mathematical and applied frameworks. The article aims to focus on a new class of 3-variable Legendre-truncated-exponential-based Sheffer sequences and to investigate their properties by means of Riordan array techniques. The quasi-monomiality of these sequences is studied within the context of Riordan arrays. These sequences are expressed in determinant forms by utilizing the relation between the Sheffer sequences and Riordan arrays. Certain special Sheffer sequences are used to construct the Legendre-truncated-exponential-based Chebyshev polynomials. The same polynomials are used as base to introduce the hybrid classes involving the exponential polynomials and the Euler polynomials of higher order as illustrative examples of the aforementioned general class of polynomials. The shapes are shown and zeros are computed for these sequences by using mathematical software. The main purpose is to demonstrate the advantage of using numerical investigation and computations to discover fascinating pattern of scattering of zeros through graphical representations. © 2019 Elsevier Inc.
Keywords: Determinant approach; Differential equations; Legendre-truncated-exponential-based Sheffer sequences; Riordan arrays; Sheffer sequences